MODEL PENGUKURAN KINERJA TENAGA KERJA OUTSOURCING PADA KONTRAKTOR UNTUK MENINGKATKAN KUALITAS BANGUNAN - -, Riman; Irawan, Dafid; Halim, Abdul (WIDYA TEKNIKA, 2014)
This study aims to provide policy recommendations that will be implemented by the "Ministry of Public Works, Construction Services Association and the Institute for Certification of Construction Services", in the standardization of the performance of labor outsourcing to contractors to improve the quality of work . The study was conducted on 21 companies outsourcing contractor who has the outsourcing, through questionnaires and interviews as well as in related institutions that contribute to determining policy. With AHP (Analytical Hierarchy Process) method, that the formulation of recommendations obtained as a step strategic, including: 1) the selection consider outsourcing more of experience, expertise and education rather than salary, 2) post acceptance of outsourcing is to conduct job orientation and training are equipped with motivation, so the reward is not the main thing, 3) coaching and directing leadership style most appropriate for outsourcing rather than supporting, 4) outsourcing performance should be evaluated periodically and provide specific action on the work as a form of attention of employers, thus dropping out of employment (severance) last action made if performance is not up to standard . KataKunci: Performance, Outsourcing, Contractor, Building, Quality.